1976
DOI: 10.1042/cs051365s
|View full text |Cite
|
Sign up to set email alerts
|

Valsalva Vasoconstrictor Reflex in Human Hypertension and after β-Adrenoreceptor Blockade in Conscious Rabbits

Abstract: for evoking graded reflex constrictor responses in 1. A Valsalva-like manoeuvre was used to elicit graded rises in total peripheral resistance (TPR) in conscious rabbits. The rises were reflex and mediated through sympathetic constrictors. Propranolol infused at different rates reaching plasma concentrations up to 240 (SEM 33) ng/ml had no effect on this reflex but reduced mean arterial pressure. However, the response was attenuated by clonidine in a dose-dependent manner. 2.Valsalva manoeuvres were used to el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This is another demonstration that the intensity of straining, translated into stroke volume reductions, conditions the vascular sympathetic activation [32]. A pharmacological approach also demonstrated the crucial role of the reflex vascular sympathetic activation during phase II, showing that a Valsalva maneuver determined profound hypotension, reaching 40 mmHg, in control subjects after alpha-adrenoceptor blockade [20,27].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is another demonstration that the intensity of straining, translated into stroke volume reductions, conditions the vascular sympathetic activation [32]. A pharmacological approach also demonstrated the crucial role of the reflex vascular sympathetic activation during phase II, showing that a Valsalva maneuver determined profound hypotension, reaching 40 mmHg, in control subjects after alpha-adrenoceptor blockade [20,27].…”
Section: Discussionmentioning
confidence: 96%
“…Many factors such as preexisting hypertension or age may affect the vascular and HR responses to the Valsalva maneuver [8,20,31]. It is evident that an autonomic neuropathy or drugs affecting the autonomic nervous system function may alter the responses to a Valsalva maneuver and supposedly to blowing notes on a wind instrument.…”
Section: Discussionmentioning
confidence: 99%
“…The three groups were studied to see if any of the changes were only seen in the hypertensive subjects, or if they were related to the rise of blood pressure right through the population. Some of the results have been briefly presented previously (Korner et al, 1976a).…”
Section: Introductionmentioning
confidence: 99%
“…1969) suggests that any effect from this action is not important. The rise in blood pressure during the effort phase of Valsalva's manoeuvre is not inhibited by (3-receptor-blocking drugs Prichard et al, 1970b), and more direct measure ments have not found any evidence of inhibition of vasoconstriction (Korner et al, 1976). No depression of the cold pressor test was seen after 3 weeks of oral propranolol in male hypertensive patients, again suggesting that the innervation of the a-receptor was not impeded (Guazzi et al, 1976).…”
Section: Adrenergic Neurone-blocking Effects O F (3-receptor-blockingmentioning
confidence: 87%